Thermal adaptation in an invasive frog (Xenopus laevis): impact of temperature on locomotion and physiology - Araspin, Laurie Nina (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.